2000
DOI: 10.1021/ja991114h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Equilibrium Constants for Reactions of α-Phenyl-Substituted Cyclopropylcarbinyl Radicals

Abstract: Laser-flash photolysis methods were used to determine Arrhenius functions for cyclizations of the 4,4-diphenyl-3-butenyl (2) and trans-4-phenyl-3-butenyl (5) radicals to the 1,1-diphenylcyclopropylcarbinyl (1) and 1-phenylcyclopropylcarbinyl (4) radicals, respectively. At 20 °C, the cyclization rate constants are 1.7 × 107 and 5.4 × 106 s-1. Equilibrium constants for the two processes were estimated and evaluated with thermochemical data and via computational methods, and Arrhenius functions for the ring-openi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 39 publications
(60 reference statements)
8
62
0
Order By: Relevance
“…This is an agreement with what Newcomb et al [32,33] reported that cyclopropylcarbinyl phenyl radical rearranges much slower than cyclopropylcarbinyl radical that has been utilized as radical clock [34] (Scheme 6). Thus, it is reasonable that ketyl radical 7 decays by reacting with solvent rather than undergoing ring opening rearrangement of its cyclopropyl moiety.…”
supporting
confidence: 90%
“…This is an agreement with what Newcomb et al [32,33] reported that cyclopropylcarbinyl phenyl radical rearranges much slower than cyclopropylcarbinyl radical that has been utilized as radical clock [34] (Scheme 6). Thus, it is reasonable that ketyl radical 7 decays by reacting with solvent rather than undergoing ring opening rearrangement of its cyclopropyl moiety.…”
supporting
confidence: 90%
“…Assuming that log A = 13.1 (Δ S ‡ = 0), we calculated the activation energy E a for each reaction. Bond dissociation energies (BDEs) are from a compendium of values52 and approximations for the C–H BDEs of the methyl group in methylcyclopropane,53 of the methyl groups in trimethylamine,54 and of the benzylic bonds in benzyl alcohol 38. Note that benzphetamine contains various C–H bonds, but the product of the P450 Compound I reaction is from hydroxylation of a methyl group adjacent to a tertiary amine 27.…”
Section: Resultsmentioning
confidence: 99%
“…Substrate relative reactivities can be anticipated from homolytic bond dissociation energies (BDEs). The BDE of a C-H bond in an N -methyl group is smaller than that of a C-H bond in a cyclopropylmethyl group, which is smaller than the BDE of an alkyl C-H bond (39,40). Thus, the rate constants for CYP119 Compound I oxidations are consistent with BDEs.…”
Section: Discussionmentioning
confidence: 95%